2008
DOI: 10.1039/b813752h
|View full text |Cite
|
Sign up to set email alerts
|

Photostability of pentacene and 6,13-disubstituted pentacene derivatives: a theoretical and experimental mechanistic study

Abstract: Computational and experimental studies have been performed to investigate the photostability of a series of 6,13-bis(arylalkynyl)-substituted pentacenes in the presence of oxygen. These studies indicate that photostabilization occurs through a selective LUMO orbital stabilization as has been seen previously for 6,13-bis(triisopropylsilylethynyl)pentacene. Marcus theory analysis suggests that the difference in vibrational reorganization energies across all compounds is small and that the thermodynamic driving f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
57
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 26 publications
4
57
0
Order By: Relevance
“…Nevertheless, it was found that BT 1 , BT 2 and BT 3 have half‐lives of around 3, 36, and 14 days, respectively, which correspond to an increased stability of 1.8, 21, and 7.6 times that of TIPS–PEN (1.7 days). As expected, there is a clear relationship between the stability and the LUMO energy level of BT materials . Remarkably, BT 1 is more stable than TIPS–PEN at the beginning of the photo‐oxidation process even though its ionization potential and electron affinity are lower.…”
Section: Resultssupporting
confidence: 67%
“…Nevertheless, it was found that BT 1 , BT 2 and BT 3 have half‐lives of around 3, 36, and 14 days, respectively, which correspond to an increased stability of 1.8, 21, and 7.6 times that of TIPS–PEN (1.7 days). As expected, there is a clear relationship between the stability and the LUMO energy level of BT materials . Remarkably, BT 1 is more stable than TIPS–PEN at the beginning of the photo‐oxidation process even though its ionization potential and electron affinity are lower.…”
Section: Resultssupporting
confidence: 67%
“…650 nm in hexanes) [58]. Several groups have also tried to vary the electronic nature of the substituents on pentacene to explore various properties [59,60,61,62,63], including the influence on stability [48,64,65]. Even so, the impact of various substitution patterns on stability as well as the mechanism of photodegradation are still not well understood [48,66].…”
Section: Pentacene-based Polycyclic Aromatic Hydrocarbon Conjugatementioning
confidence: 99%
“…Electron transfer rates from excited-state pentacenes are also observed to be fast and solvent-dependent. [ 3 ] Deactivation of the initial singlet state by mechanisms which can compete with O 2 activation therefore serves to increase photostability. The main non-radiative mechanism for this is singlet fi ssion [ 10,11 ] via interaction with a second TIPS-pentacene molecule to produce a pair of triplets.…”
Section: Concentration-and Solvent-dependent Photochemical Instabilitmentioning
confidence: 99%
“…Pentacene for example has a very short half-life in solution under the infl uence of light; this behaviour can be attenuated markedly by derivatisation at the 6-and 13-positions. [1][2][3] As a consequence, materials such as 6,13-bis(triisopropylsilylethynyl)pentacene (TIPS-pentacene) are becoming popular replacements for pentacene in electronic devices. [ 4,5 ] However, these derivatives are themselves still prone to photochemical degradation during processing, which potentially perturbs both the optical absorption and electronic properties of fi lms cast from solution.…”
mentioning
confidence: 99%
See 1 more Smart Citation